Ethical orientations of young women in Poland and Serbia. Comparative studies - Mariola Chomczyńska-Rubacha; Krzysztof Rubacha (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
The article is a report of a comparative study of the ethical orientations of women in Poland and Serbia. We have two ethical orientations in the theoretical sense: focused on justice and care. Social context to compare is a situation of women and their rights in Poland and Serbia. We ask about the differences in ethical orientations of women in Poland and Serbia. Our results shows, that women from Poland has higher indication justice ethical orientation, then Serbian women. However this relation isn't simple.